AB0277 Assessment of global disease activity in RA patients monitored in the meteor database: The patient's versus the rheumatologist's opinion. (23rd January 2014) - Gvozdenović, E.; Koevoets, R.; van der Heijde, D.; Huizinga, T.; Allaart, R.; Landewé, R.
Abstract : Background: Disagreement on disease activity between rheumatoid arthritis (RA) patients and rheumatologists may influence treatment decisions and compliance. Objectives: To compare -and identify determinants of- the assessment of disease activity on a visual analogue scale (VAS, 0=best possible, 100=worst possible) by patients (VAS-pt) and physicians (VAS-phy), and to investigate if they are influenced by time. Methods: Anonymous data were used from 2118 Dutch patients included in the METEOR database, a worldwide online tool for disease monitoring in RA. Intra-class correlation coefficients (ICC) were calculated as a measure of agreement and a Bland Altman plot was created to visualize the differences between VAS-pt and VAS-phy. Linear Mixed Model analysis was used to model the VAS-pt and VAS-phy over time. Gender, age, HAQ, swollen joint count, tender joint count, VAS pain, disease duration and BSE were considered as possible determinants of the VAS-pt or VAS-phy. Results: Mean age was 57 years (SD: 15) and 67% of the patients were female. Correlation between VAS-pt and VAS-phy was moderate (ICC 0.61; p<0.01). Patients score on average 11 points higher (worse) than rheumatologists at the first registered visit (95% limits of agreement: -25.2 to 47.6). Scores were increasingly discordant towards the higher end of the scale. Both VAS-phy and VAS pt increase by the tender joint count, HAQ-score and patient's VAS for pain. VAS-phy, but not VAS-pt, also increases by swollen joint count. VAS-phy decreases by disease duration, and VAS-pt showed a similar trend. Conclusions: Patients score VAS disease activity systematically higher than rheumatologists, although patients' and physicians' VAS are more or less associated with the same determinants: HAQ-score, tender joint count and VAS pain. But physicians put more weight on swollen joint count, and score lower disease activity over time, whilst patients do not. Disclosure of Interest: None Declared